MODERNIST ELEMENTS IN WESTERN AND EASTERN LITERATURE A CONTEXTUAL ANALYSIS IN LITERARY PROCESS - Saparniyazov Omirbek Nukusbayevich (Sciental Journals Publishing, 2025)
This article provides a scientific-theoretical analysis of the formation of modernism within Western and Eastern literature, its ideological-aesthetic principles, and how literary examples created in this direction have been interpreted in a cultural context. The research examines the interconnections and differences between Western modernism's characteristics—such as psychological analysis, formal innovation, fragmentary plots, and individualistic spirit—and the socio-spiritual directions formed in Eastern literature on a contextual basis. The article studies changes in literary thinking based on mutual cultural influences, specificities of national literary spaces, and modernism's internal evolutionary tendencies.
Keywords: Modernism, literary thinking, contextual analysis, Western literature, Eastern literature, aesthetic criteria, individualism, psychological portrait, artistic experiment, genre transformation